A mathematical model of transmission of rice tungro diseases by nephotettix virescens - Blas, Nikki T. (Institute of Mathematics, College of Science, University of the Philippines Diliman, 2015)
One of the major threats in rice agriculture is the tungro virus, which is transmitted semi-persistently to rice plants via green rice leafhoppers called nephottetix virescens. Tungro is polycyclic and complex disease of rice associated by dual infection with Rice Tungro Bacilliform Virus (RTBV) and Rice Tungro Spherical Virus (RTSV). Interaction of the two viruses results in the degeneration of the host. In this paper, we used a plant-vector system of ordinary differential equations to model the spread of the disease in a model rice field. Parameter values were obtained from studies on the entomology of Nephottetix Virescens and infection rates of RTSV and RTBV. The system was analyzed for equilibrium solutions, and solved numerically for resistant and susceptible rice varieties.